PTH Is a Promising Auxiliary Index for the Clinical Diagnosis of Aldosterone-Producing Adenoma. (24th August 2015) - Zhang, Lin-Xi; Gu, Wei-Jun; Li, Yi-Jun; Wang, Yang; Wang, Wen-Bo; Wang, An-Ping; Shen, Lei; Zang, Li; Yang, Guo-Qing; Lu, Zhao-Hui; Dou, Jing-Tao; Mu, Yi-Ming
Abstract : BACKGROUND: Parathyroid hormone (PTH) stimulates aldosterone secretion in human adrenocortex and is regulated by the renin-angiotensin-aldosterone system. We speculated that measurement of PTH may be a valuable aid in the diagnosis of aldosterone-producing adenoma (APA). METHODS: To test this hypothesis, we recruited 142 patients with adrenal adenoma, of whom 84 had an APA and 58 had a nonfunctioning adrenal adenoma (NFA). Plasma levels of intact PTH, serum potassium, sodium, calcium, phosphate, 25(OH) vitamin D, plasma aldosterone concentration (PAC), plasma renin activity (PRA), and aldosterone to renin ratio (ARR) were measured in every patient. Computed tomography (CT) scanning of the adrenal gland and adrenal hormone levels was used to evaluate the function of the adrenal adenoma. We also evaluated the impact of renin-angiotensin-aldosterone system (RAAS) components on PTH from the recumbent-upright test in 15 patients with APA and 30 patients with NFA. RESULTS: Compared with NFA, PTH levels were significantly increased in patients with APA, and serum calcium and phosphate were significantly decreased. When position was changed from supine to upright, the variation in PTH levels was significantly higher in APA patients compared with NFA patients. Receiver operator characteristic (ROC) curves identified the Youden index, which corresponded to the best tradeoff of combined marker (ARR and PTH) with a sensitivity and specificity of 89.3% and 93.1%, respectively. CONCLUSIONS: The baseline and positional variation of serum PTH levels were significant in APA, thus PTH may be a promising auxiliary index for the clinical diagnosis of APA.